Implementation of the Tourism Development Master Plan Policy in the Tourism Village of Kepuharjo, Cangkringan District, Sleman Regency - Endah Neni Miyayi (Soshum: Jurnal Sosial dan Humaniora, 2021)
Based on Law Number 23 of 2014, the potential for improving community welfare is an optional affair by the government. This encourages every local government to develop a tourist village. Therefore, this study provides an overview of the application of the rules in order to develop the Kepuharjo Tourism Village in Cangkringan District, Sleman Regency. Furthermore, this study uses the type of rule application from George C. Edward III. In the preparation of this research, the researcher used a descriptive qualitative approach. This means that the types of data sources used are primary and secondary data. Based on the results of interviews and observations, it can be concluded that the implementation of the policy for developing the Tourism Village of Kepuharjo Village is not optimal. The implementation of the program is not optimal because there are several factors that influence the development of tourism villages, namely from the resources and bureaucratic structures. Meanwhile, the driving factors for the development of the tourism village are aspects of communication and disposition.